Chất lượng kiểm toán và chi phí sử dụng nợ: Bằng chứng thực nghiệm tại Việt Nam - Nguyễn Vĩnh, Khương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
The study aims at providing empirical evidences of the impact of audit quality on cost of debt in Vietnam Based on the data collected from 241 listed firms on the Vietnam stock exchange in the period of 2010- 2016, we use quantitative research method to desmonstrate the negative impact of audit quality on cost of debt From the results, the paper suggests some implications for the financial statement disclosure of listed firms' and regulators' in order to contribute to the transparency of the financial reports
Keywords: Audit quality; Cost of debt; Listed firm; Vietnam